2000
DOI: 10.1034/j.1600-0404.2000.101004259.x
|View full text |Cite
|
Sign up to set email alerts
|

Is there any change of stroke incidence during Ramadan?

Abstract: Ramadan is a special month for Muslims, as fasting during Ramadan is a religious duty. In this study we investigated whether stroke incidence differs during Ramadan compared to other months. All patients with stroke admitted to any hospital in the Isparta Province between 1991-1995 were included in this study. Patients were divided into 2 groups according to the month of onset of stroke. The first group included patients with strokes that occurred in Ramadan and the second group strokes with onset in other mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 0 publications
5
42
1
1
Order By: Relevance
“…Most of the previous studies compared heterogeneous groups of patients (both ischemic stroke and intracerebral hemorrhage),20 and did not include a non‐fasting group at the time of Ramadan 19, 21, 22…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the previous studies compared heterogeneous groups of patients (both ischemic stroke and intracerebral hemorrhage),20 and did not include a non‐fasting group at the time of Ramadan 19, 21, 22…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors include medical conditions (hypertension, diabetes mellitus, dyslipidemia, atrial fibrillation, sleep apnea, and others), lifestyle (smoking, physical activity)12, 13 and environmental factors (air temperature and air pollution14, 15, 16, 17, 18). Ramadan associated changes such as poor drug therapy compliance; reduced glycemic control, and dehydration may temporarily contribute to stroke risk, yet such an increased stroke risk during Ramadan has not been reported 19, 20, 21, 22…”
mentioning
confidence: 99%
“…Increased blood viscosity secondary to dehydration may enhance the risk of thrombosis. A report from Saudi Arabia suggested an increased incidence of retinal vein occlusion in patients who fasted during Ramadan (17). However, hospitalizations due to coronary events or stroke were not increased during Ramadan (18,19).…”
Section: Dehydration and Thrombosismentioning
confidence: 99%
“…But we would stress that Qatar is more developed country especially in the health system and cooling technology than our country and the method and design of the study were different than that of our study. Akhan et al 4 (2000) also reported no increase in the incidence of hospitalization of stroke cases during Ramadan mostly because he performed his study in Isparta where the environmental factors are quite different than that of our region. Nearly the same results mentioned by Ahmad Chistaz and his colleagues 7 in Iran, in which he studied the rate of stroke between fasting and nonfasting population and no significance difference was observed over two years, possibly because Iran is a different country than Iraq regarding its weather.…”
Section: Hemorrhagic 4mentioning
confidence: 99%
“…Fasting during Ramadan is a radical change in lifestyle for the period of a lunar month. [1][2][3][4] The time of observance differs each year because it follows the lunar calendar, where the time periods corresponding to the month of Ramadan is different in every year according to the solar calendar, since the lunar calendar is 11-12 days shorter than the solar year. 5 The fasting period from sunrise to sunset varies with the geographical site and seasons.…”
Section: Introductionmentioning
confidence: 99%